Crise économique et consensus en État rentier : le cas de l'Algérie socialiste (Note) - Garon, Lise (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1994)
Like other oil-producing Arab countries, socialist Algeria has followed a specific line of development : that of the rentier State. Its economy has been characterized by dependence on oil revenues which account for 98 % of all export earnings. Among the elites and the population, this income has served to maintain a consensus around the government's power. What happens, however, when the rentier State loses this consensus ? The case of socialist Algeria suggests that the rentier State would then be forced to use up its income, thereby bringing about its disappearance. This unprecedented case may by repeated in other states. Algeria's experience may thus provide us with lessons for understanding the rentier State and the « democratic transition ».